Cloning and sequence variation analysis of candidate genes involved in nitrogen metabolism in potato (Solanum tuberosum) - TIWARI, JAGESH KUMAR; DEVI, SAPNA; ALI, NILOFER; DUA, VIJAY K; SINGH, RAJESH K; CHAKRABARTI, SWARUP K (The Indian Journal of Agricultural Sciences, 2018)
Objective of this study was to isolate, sequence and analyze variations in candidate genes involved in nitrogen (N) metabolism in potato (Solanum tuberosum L.) for future breeding application. Two contrasting potato varieties, viz. Kufri Gaurav (N efficient) and Kufri Jyoti (N inefficient) were used. Of the total 17 PCR primers tested for N metabolism genes in the both varieties and only 12 distinct bands were cloned and sequenced, which were amplified by six primers of five genes (nitrate transporter-NRT, ammonium transporter-AMT, nitrate reductase-NR, nitrite reductase-NIR and asparagines synthetase-AS). Following sequence analysis, non-redundant sequences with uninterrupted open reading frames of 12 ‘N-homologous genes’ were identified to the known N metabolic pathway genes. Thus, the identified 12 N-homologous genes may serve as an important genomic resource for novel gene/marker discovery and would be useful for marker-assisted selection (MAS) in potato with better nitrogen use efficiency (NUE).